An Efficient Method for Approximately Simulating Drainage Capability for Urban Flood - Li, Donglai; Hou, Jingming; Xia, Junqiang; Tong, Yu; Yang, Dong; Zhang, Dawei; Gao, Xujun (Frontiers in Earth Science, 2020)
Assessing the performance and capability of drainage pipes is of significance for computing urban flooding. However, drainage-pipe data is not available for most urban areas, therefore raising the problem for computing the drainage capability in an approximate way. To resolve this problem, a new type of approach that improves on the existing approach, termed the inlet-drainage approach, is proposed by assuming the drainage effects as a mass subtracted in particular parts, e.g., the area with gullies or inlets. The proposed approach is incorporated into a 2D hydrodynamic model for surface flow to simulate the coupled rainfall-runoff-drainage-inundation processes. Through validation against the measured and modeled results in two test cases involving ideal and realistic urban catchments, it is demonstrated that the proposed new approach could provide fairly good modeled results for computing drainage effects. More importantly, the new approach is simple and easy to implement.